2020
DOI: 10.1021/acsnano.0c04099
|View full text |Cite
|
Sign up to set email alerts
|

Photothermoelectric Response of Ti3C2Tx MXene Confined Ion Channels

Abstract: With recent growing interest in biomimetic smart nanochannels, a biological sensory transduction in response to external stimuli has been of particular interest in the development of biomimetic nanofluidic systems. Here we demonstrate the MXene-based subnanometer ion channels that convert external temperature changes to electric signals via preferential diffusion of cations under a thermal gradient. In particular, coupled with a photothermal conversion feature of MXenes, an array of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 57 publications
0
89
0
Order By: Relevance
“…Hong et al reported the sub-nano ion channel based on 2D-TMCs, which can convert external temperature changes into electrical signals through the preferential diffusion of cations under a thermal gradient. Based on the photothermal conversion of MXenes, the Ti 3 C 2 T x ion channel can capture the diffusion potential across the nanochannel under the axial temperature gradient of the light drive and exhibit the photothermoelectric ionic response of 1 mV K -1 [215].…”
Section: Other Potential Applicationsmentioning
confidence: 99%
“…Hong et al reported the sub-nano ion channel based on 2D-TMCs, which can convert external temperature changes into electrical signals through the preferential diffusion of cations under a thermal gradient. Based on the photothermal conversion of MXenes, the Ti 3 C 2 T x ion channel can capture the diffusion potential across the nanochannel under the axial temperature gradient of the light drive and exhibit the photothermoelectric ionic response of 1 mV K -1 [215].…”
Section: Other Potential Applicationsmentioning
confidence: 99%
“…56 Hong et al reported that an array of nanoconfined Ti 3 C 2 T x ion channels could capture transnanochannel diffusion potentials under a light-driven axial temperature gradient. 37 The thermoelectric Page 8 of 25 CCS Chemistry response of MXene nanofluidics was calculated to reach up to 1.0 mV•K −1 under local sunlight exposure (Fig. 4a).…”
Section: Photoelectric Effectmentioning
confidence: 99%
“…To date, three different mechanisms, including photochemical, 35,36 photoelectrical, 8,22 and photothermal effects, 37,38 have been proposed to explain the light-driven ion transport phenomenon (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Salinity gradient energy, the Gibbs free energy [204] in the salt solutions of varying concentrations, is known as the blue energy and can be converted into electrical energy by reverse electrodialysis (RED) [205,206]. Considering the great potential of marine resources, the salinity gradient has great potential in alleviating the energy crisis in the future.…”
Section: Salinity Gradient Energy Conversionmentioning
confidence: 99%